Mycobacterium tuberculosis genetic diversity and drug resistance across Portuguese-speaking countries and CPLP-TB: a novel framework and surveillance tool for the Lusophone community - Perdigão, João (2020)
Background: Tuberculosis (TB) remains a major health problem within the Community of Portuguese Language Speaking Countries (CPLP). Despite the marked variation in TB incidence across its member-states and continued human migratory flux between countries, a considerable gap in the knowledge on the Mycobacterium tuberculosis population structure and strain circulation between the countries still exists. Materials and Methods: To address this, we have assembled and analyzed the largest CPLP M. tuberculosis molecular and drug susceptibility dataset, comprised by a total of 1447 clinical isolates, including 423 multidrug-resistant isolates, from five CPLP countries. Genotyping analysis was carried out by 15/24 Mycobacterial Interspersed Repetitive Unit – Variable Number of Tandem Repeat (MIRU-VNTR) and Spoligotyping. Drug Susceptibility testing was performed using standardized BACTEC 960 MGIT methodology or through the resazurin microtiter assay (REMA). Results: The data herein presented reinforces Latin American and Mediterranean (LAM) strains as the hallmark of M. tuberculosis populational structure in the CPLP coupled with country-specific differential prevalence of minor clades. Moreover, using high-resolution typing by 24-loci MIRU-VNTR, six cross-border genetic clusters were detected, thus supporting recent clonal expansion across the Lusophone space. To make this data available to the scientific community and public health authorities we developed CPLP-TB (available at http://cplp-tb.ff.ulisboa.pt), an online database coupled with web-based tools for exploratory data analysis. Conclusions: As a public health tool, CPLP-TB is expected to contribute to improved knowledge on the M. tuberculosis population structure and strain circulation within the CPLP, thus supporting risk assessment of strain-specific trends.